2013
DOI: 10.1186/1559-4106-8-31
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of calcium content in bone by using ToF-SIMS–a first approach

Abstract: The determination of the spatially resolved calcium distribution and concentration in bone is essential for the assessment of bone quality. It enables the diagnosis and elucidation of bone diseases, the course of bone remodelling and the assessment of bone quality at interfaces to implants. With time-of-flight secondary ion mass spectrometry (ToF-SIMS) the calcium distribution in bone cross sections is mapped semi-quantitatively with a lateral resolution of up to 1 μm. As standards for the calibration of the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Twenty-five kiloelectronvolt Bi þ 3 primary ions were used for ToF-SIMS imaging, for sputtering, a 1 keV O þ 2 beam was used. [26,29]. These characteristic peaks and fragmentation patterns of collagen and HAP were also obtained from mineralized bone tissue.…”
Section: Structure Of Cortical Bonementioning
confidence: 71%
See 1 more Smart Citation
“…Twenty-five kiloelectronvolt Bi þ 3 primary ions were used for ToF-SIMS imaging, for sputtering, a 1 keV O þ 2 beam was used. [26,29]. These characteristic peaks and fragmentation patterns of collagen and HAP were also obtained from mineralized bone tissue.…”
Section: Structure Of Cortical Bonementioning
confidence: 71%
“…Therefore, appropriate standards that possess a nearly identical composition as the analysed material are required. Henss et al [29] showed successful quantification of calcium in bone by ToF-SIMS, using standards with an almost identical composition as natural bone.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the gender change we also included some complementary methods. One of them was “time of flight secondary ion mass spectrometry” (ToF-SIMS) for quantification of bone calcium ion (Ca 2+ ) content and proline fragments that is one of the main amino acids of collagen [ 13 - 16 ]. The principle of ToF-SIMS is that primary ions hit the sample surface, releasing secondary ions from the surface, that were collected by an analyzer for producing single mass spectra and mass images of the sample surface [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…[71][72][73] Minakata et al 71 applied MALDI-Q-TOF to quantify Au and Pt in tissues aer complexation with DDC. The use of other MS instrumentation for the analysis of biological tissues was demonstrated in three reports.…”
Section: Solid Sample Introductionmentioning
confidence: 99%